Direct imaging of Indium-rich triangular nanoprisms self-organized formed at the edges of InGaN/GaN core-shell nanorods. Issue 1 (December 2018) - Schmidt, Gordon; Müller, Marcus; Veit, Peter; Metzner, Sebastian; Bertram, Frank; Hartmann, Jana; Zhou, Hao; Wehmann, Hergo-Heinrich; Waag, Andreas; Christen, Jürgen
Abstract Higher indium incorporation in self-organized triangular nanoprisms at the edges of InGaN/GaN core-shell nanorods is directly evidenced by spectral cathodoluminescence microscopy in a scanning transmission electron microscope. The nanoprisms are terminated by three 46 nm wide a-plane nanofacets with sharp interfaces forming a well-defined equilateral triangular base in the basal plane. Redshifted InGaN luminescence and brighter Z-contrast are resolved for these structures compared to the InGaN layers on the nanorod sidewalls, which is attributed to at least 4 % higher indium content. Detailed analysis of theinner optical and structural properties reveals luminescence contributions from 417 nm up to 500 nm peak wavelength proving the increasing indium concentration inside the nanoprism towards the nanorod surface.